Protection Of Customers for Management of Digital Banking Services (Study at PT. BRI Unit Boyolali) - Herdian Ayu Andreana Beru Tarigan; Darminto Hartono Paulus (Hang Tuah Law Journal, 2019)
Increasing competition in the Indonesian banking industry has encouraged many banks to improve the quality of services to customers by utilizing information technology developments. Service innovation in the use of information technology encourages banks to enter the era of digital banking services. However, the development of digital banking services also increases the risks faced by banks. The purpose of this study is to provide an overview of the implementation of digital banking services and customer protection for risks from digital banking services. The method used in this study is an empirical legal research method. The results of this study indicate that the implementation of digital banking services is regulated by OJK Regulation No.12/POJK.03/2018. The existence of this OJK Regulation is expected by banks as providers of digital banking services to always prioritize risk management in the use of information technology. In addition, this study also shows the existence of 2 types of customer protection for the use of digital banking services, namely preventive protection in the form of legislation related to customer protection in the financial services sector and repressive protection in the form of bank accountability for complaints from customers using digital banking services.